Histones and their chaperones: Adaptive remodelers of an ever-changing chromatinic landscape - Torres-Arciga, Karla; Flores-León, Manuel; Ruiz-Pérez, Samuel; Trujillo-Pineda, Magalli; González-Barrios, Rodrigo; Herrera, Luis A. (Frontiers in Genetics, 2022)
Chromatin maintenance and remodeling are processes that take place alongside DNA repair, replication, or transcription to ensure survival and adaptability of a cell. The environment and the needs of the cell dictate how chromatin is remodeled; particularly where and which histones are deposited, changing the canonical histone array to regulate chromatin structure and gene expression. Chromatin is highly dynamic, and histone variants and their chaperones play a crucial role in maintaining the epigenetic regulation at different genomic regions. Despite the large number of histone variants reported to date, studies on their roles in physiological processes and pathologies are emerging but continue to be scarce. Here, we present recent advances in the research on histone variants and their chaperones, with a focus on their importance in molecular mechanisms such as replication, transcription, and DNA damage repair. Additionally, we discuss the emerging role they have in transposable element regulation, aging, and chromatin remodeling syndromes. Finally, we describe currently used methods and their limitations in the study of these proteins and highlight the importance of improving the experimental approaches to further understand this epigenetic machinery.